Introduction to linear regression analysis - Montgomery, Douglas C.; Peck, Elizabeth A., 1953-; Vining, G. Geoffrey, 1954- (Hoboken, NJ : Wiley, 2012)
'This book describes both the conventional and less common uses of linear regression in the practical context of today's mathematical and scientific research'--
Includes bibliographical references (pages 628-641) and index.
Keywords: Regression analysis